Laboratories of Reproductive Justice: State Amendments and the Right to Paid Family Leave - Pamela Chen (Columbia Journal of Gender and Law, 2025)
This Note proposes legal strategies for recognizing paid family leave as a constitutional entitlement under state law. Long viewed as laboratories for democratic experimentation, states can play a central role in areas where federal protections remain limited. In the aftermath of Dobbs v. Jackson Women’s Health Organization, several states—including Maryland, Michigan, Missouri, Montana, Ohio, and Vermont—amended their constitutions to guarantee a right to “reproductive freedom.” This Note argues that these amendments create fertile ground for rights development and should be read to include an affirmative right to paid family leave. Drawing on a reproductive justice framework, which defines reproductive autonomy as the ability to have children, not have children, and parent children in safe and sustainable conditions, this Note analyzes the text of these amendments and the historical landscape of state positive-rights jurisprudence.